Commensuration and styles of reasoning: Venice, cost–benefit, and the defence of place - Samiolo, Rita (Accounting, Organizations and Society, 2012)
This paper discusses some preconditions for “making things the same” by means of quantification and economic calculation. It examines a controversial cost–benefit analysis, conducted as part of the environmental appraisal of a large public sector project in Italy: the long-debated scheme for flood protection in Venice. By tracing the different “styles of calculation” that characterised the economic and environmental appraisal of the project, the paper analyses the inter-relationship between economic representations of the urban and natural environment, its political symbolism, and various attempts to intervene upon it. It follows how the objectivity of numbers is debated, stabilised or disrupted, as differing appeals to realism and accuracy are advanced in the context of different modes of intervention and practical aims. The paper shows that the “commensuration” and “standardisation” that numbers can bring about rest on how the object of calculation as well as, crucially, its subject are represented and conceived.